Проблемы и решения в области охраны окружающей среды в Республике Карелии - Shegelman I. R., Petukhov R. A. (Education and science in the modern context, 2018)
the regional plan in the Republic of Karelia in 2017 included 57 major events and events, about 60,000 people took part, and more than 25,000 children and adolescents in environmental education activities.
Keywords: охрана окружающей среды; Республика Карелии